Pembuatan dedak padi fermentasi dan penggunaannya pada pakan ayam kampung: Fermented Rice Bran Making and Its Use in Native Chicken Feed - Theresia N. I. Koni; Agustinus Paga; Asrul Asrul; Melkianus D.S Randu; Tri A.Y. Foenay (IGKOJEI: Jurnal Pengabdian Masyarakat, 2026)
ABSTRACT Kampoeng chickens are widely raised across Indonesia and represent an important source of animal protein and household income in rural communities. Their productivity is closely associated with the quantity and quality of feed. Rice bran is an inexpensive and readily available feed ingredient; however, its inclusion in poultry diets is generally limited to approximately 10% because of its high crude fiber content (25–27%) and phytic acid concentration (7.39 mg/100 g), which reduce nutrient utilization. Previous research demonstrated that fermenting rice bran with palmyra sap effectively reduced crude fiber and phytic acid levels, thereby improving its nutritional value and allowing its inclusion to be increased to 20% in kampoeng chicken diets without compromising growth performance. These findings were disseminated through a community engagement program involving 15 members of the Elshadday UMKM, a kampoeng chicken farmer association located in Teun Baun Village, West Amarasi District, Kupang Regency. The program aimed to enhance farmers' knowledge and technical skills in producing fermented rice bran and utilizing it as a feed ingredient in kampoeng chicken rations. The activities consisted of educational counseling, group discussions, and on-farm demonstration plots. Participants received both theoretical instruction and hands-on training in the fermentation of rice bran using palmyra sap, feed formulation, and feed preparation. The program substantially improved farmers' knowledge, with understanding of rice bran fermentation increasing by 100% and knowledge of feed formulation and feed manufacturing increasing by 66.67%. By the end of the program, participants were able to formulate native chicken diets containing up to 20% palmyra sap-fermented rice bran. These results demonstrate that integrating research outcomes with community-based training is an effective approach to promoting the adoption of locally available feed technologies and improving the capacity of smallholder poultry farmers. Keywords: Fermentation; Native chicken feed; Palmyra sap; Rice bran; UMKM Elshadday ABSTRAK Ayam kampung merupakan komoditas unggas lokal yang tersebar luas diberbagai wilayah di Indonesia. Produktivitas ayam kampung dipengaruhi oleh kuantitas dan kualitas pakan. Pakan ayam tersusun dari berbagai bahan pakan, seperti jagung dan dedak padi. Dedak padi diperoleh dengan harga yang murah dan digunakan 10% dalam pakan ayam. Terbatasnya penggunaan dedak padi karena kandungan serat kasar 25-27% dan kadar asam fitat 7,39 mg/100g. Proses fermentasi dedak padi dengan nira lontar terbukti efektif menurunkan kandungan serat kasar dan asam fitat. Peningkatan kualitas nutrisi tersebut memungkinkan dedak padi terfermentasi dimanfaatkan hingga taraf 20% dalam pakan ayam kampung tanpa menurunkan performa ternak. Hasil penelitian ini diimplementasikan kepada kelompok peternak mitra yang terdiri atas 15 anggota UMKM Elshadday yang bergerak dalam usaha pemeliharaan ayam kampung. Kelompok mitra tersebut berlokasi di Desa Teun Baun, Kecamatan Amarasi Barat, Kabupaten Kupang. Kegiatan pengabdian ini bertujuan untuk meningkatkan pengetahuan dan keterampilan peternak dalam mengolah dedak padi melalui teknologi fermentasi serta memanfaatkannya sebagai bahan baku penyusunan ransum ayam kampung. Metode yang digunakan dalam kegiatan pengabdian ini adalah penyuluhan,  diskusi kelompok, dan demonstrasi plot (demplot). Selama program, para petani diberikan pengetahuan dan keterampilan praktis tentang pengolahan dedak padi melalui fermentasi menggunakan nira lontar dan pemanfaatan dedak padi fermentasi sebagai komponen pakan ayam kampung. Program ini secara efektif meningkatkan pengetahuan peserta, tentang fermentasi dedak padi menggunakan nira lontar meningkat sebesar 100% dan pengetahuan tentang formulasi pakan dan pembuatan pakan meningkat sebesar 66,67%. Peternak dapat membuat pakan ternak ayam kampung dengan menggunakan dedak padi hasil fermentasi dengan nira lontar sebesar 20% dalam pakan. Kata kunci: Dedak padi; Fermentasi; Nira lontar; Pakan ayam kampung; UMKM Elshadday